2018
DOI: 10.1016/j.biopsych.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Familial Liability to Epilepsy and Attention-Deficit/Hyperactivity Disorder: A Nationwide Cohort Study

Abstract: This study demonstrates a strong and etiologically complex association between epilepsy and ADHD, with shared familial factors and risk factors unique to the individual contributing to co-occurrence of the disorders. Our findings suggest that epilepsy and ADHD may share less genetic risk as compared with other neurodevelopmental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 53 publications
2
41
0
2
Order By: Relevance
“…Prevalence of ADHD in children with epilepsy is reported as 30%‐40% in targeted studies and 12.5%‐15% in a nontargeted, population registry study, overall a rate 2.5 to 5.5 times higher than in otherwise healthy children without seizures. Attention problems often predate onset of seizures . The predominantly inattentive type of ADHD is more prevalent in patients with epilepsy .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalence of ADHD in children with epilepsy is reported as 30%‐40% in targeted studies and 12.5%‐15% in a nontargeted, population registry study, overall a rate 2.5 to 5.5 times higher than in otherwise healthy children without seizures. Attention problems often predate onset of seizures . The predominantly inattentive type of ADHD is more prevalent in patients with epilepsy .…”
Section: Introductionmentioning
confidence: 99%
“…Attention problems often predate onset of seizures. 6,7 The predominantly inattentive type of ADHD is more prevalent in patients with epilepsy. 5,9,10 A large, population-based cohort study has suggested that both genetic and environmental factors contribute to this comorbidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few twin and family studies have explored how genetic factors contribute to non-psychiatric comorbidity. The literature suggests novel etiologic links with asthma [64], obesity [65], and epilepsy [66].…”
Section: Psychiatric Comorbiditymentioning
confidence: 99%
“…Patients with epilepsy have a three‐ to five‐fold increased risk of attention‐deficit/hyperactivity disorder (ADHD) diagnosis, and 20%‐50% of children with epilepsy exhibit subclinical ADHD symptoms . Untreated, ADHD is associated with severe adverse outcomes, making effective treatment crucial.…”
Section: Introductionmentioning
confidence: 99%